Influence of powderedÂ Moringa oleiferaÂ seeds and natural filter media on the characteristics of tapioca starch wastewater - Nur Hidayat; Esti Rosaliana (International Journal of Recycling of Organic Waste in Agriculture)
Background: Moringa oleifera tree is indigenous and highly abundant in Indonesia and its seeds are widely known to be used as a natural coagulant for treating wastewater. Wastewater from tapioca starch industry, particularly in Indonesia, which contains high organic matters, was revealed by high biochemical oxygen demand (BOD) and chemical oxygen demand (COD) value. In this study the combination of powdered M. oleifera seed and natural filter media was studied. A laboratory scale of tapioca starch wastewater (TSW) treatment was designed using a continuous two-stage clarifier tanks filled with sand or coconut fibre combined with the addition of powdered M. oleifera seed. Results: A significant improvement on both the physical and chemical characteristics of the effluent quality, showing a clearer colour and a greater reduction in BOD, COD and total suspended solid values; while pH was in the acceptable range for effluent disposal. In terms of the microbial characteristics, all treatments gave slightly higher counts of total coliform in the range of 26 to 40 MPN 100 mlâ1 . Conclusions: The combination of two-stage clarifier tank with natural filter media and the use of M. oleifera as natural coagulant gave a significant improvement in the quality and appearance of TSW final effluent.